2023
DOI: 10.1186/s40538-023-00387-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chitosan nanoparticles on quality indices, metabolites, and vase life of Rosa hybrida cv. Black magic

Abstract: Background Chitosan nanoparticles (CTS-NPs) protect the active ingredients from the environment for a specific period and reduces sweating, control weight loss, delay ripening, and increase vase life. So, a factorial experiment was carried out as a randomized complete design in three replications to investigate the efficiency of CTS-NPs in quality improvement and longevity extension of cut rose flowers. Results The 15-day maximum vase life was atta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…Senescence of cut flowers is affected by an increase in membrane lipid peroxidation and free radicals, including H 2 O 2 , as well as its final product MDA in petals, such as rose, carnation, tree peony, and Strelitzia reginae L ( Hassan et al., 2014 ; Shi et al., 2015 ; Aalifar et al., 2020 ; Thakur et al., 2022 ). Antioxidant defense systems such as SOD, CAT, and POD are employed in plant cells that can be protected from the danger of reactive oxygen species (ROS) ( Shi et al., 2015 ; Hasanuzzaman et al., 2020 ; Zulfiqar and Ashraf, 2021 ; Seyed Hajizadeh et al., 2023 ). Many studies have shown that Ag-NPs play an important role in limiting H 2 O 2 levels and reducing MDA production by inhibiting bacterial growth at the stem ends, thereby extending the life of cut flowers ( Hassan et al., 2014 ; Rashidiani et al., 2020 ; Anvari et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Senescence of cut flowers is affected by an increase in membrane lipid peroxidation and free radicals, including H 2 O 2 , as well as its final product MDA in petals, such as rose, carnation, tree peony, and Strelitzia reginae L ( Hassan et al., 2014 ; Shi et al., 2015 ; Aalifar et al., 2020 ; Thakur et al., 2022 ). Antioxidant defense systems such as SOD, CAT, and POD are employed in plant cells that can be protected from the danger of reactive oxygen species (ROS) ( Shi et al., 2015 ; Hasanuzzaman et al., 2020 ; Zulfiqar and Ashraf, 2021 ; Seyed Hajizadeh et al., 2023 ). Many studies have shown that Ag-NPs play an important role in limiting H 2 O 2 levels and reducing MDA production by inhibiting bacterial growth at the stem ends, thereby extending the life of cut flowers ( Hassan et al., 2014 ; Rashidiani et al., 2020 ; Anvari et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…After culturing, the samples were incubated at 37ºC for 48 h. The number of microorganisms present in the preservative solutions was determined by counting the former colony units post-incubation. These were recorded as colony-forming units per milliliter (CFU mL −1 ), as described by Seyed Hajizadeh et al [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Chitosan can be formulated into nanoparticles, microspheres, or hydrogels, which can control the release of drugs over a period of hours to weeks [64]. In the last few years, it has been widely used to obtain nanoparticles that have antioxidant properties [65][66][67][68][69][70][71][72][73][74][75][76][77][78]. Alginate is a natural polysaccharide that is derived from seaweed.…”
Section: Polysaccharidesmentioning
confidence: 99%